A death in Cornwall [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series, 2024)
Art restorer and legendary spy Gabriel Allon has slipped quietly into London to attend a reception at the Courtauld Gallery celebrating the return of a stolen self-portrait by Vincent van Gogh. But when an old friend from the Devon and Cornwall Police seeks his help with a baffling murder investigation, he finds himself pursuing a powerful and dangerous new adversary. The victim is Charlotte Blake, a celebrated professor of art history from Oxford who spends her weekends in the same seaside village where Gabriel once lived under an assumed identity. Her murder appears to be the work of a diabolical serial killer who has been terrorizing the Cornish countryside. But there are a number of telltale inconsistencies, including a missing mobile phone. And then there is the mysterious three-letter cypher she left behind on a notepad in her study. Gabriel soon discovers that Professor Blake was searching for a looted Picasso worth more than a $100 million, and he takes up the chase for the painting as only he can, with six Impressionist canvases forged by his own hand and an unlikely team of operatives that includes a world-famous violinist, a beautiful master thief, and a lethal contract killer turned British spy. The result is a stylish and wildly entertaining mystery that moves at lightning speed from the cliffs of Cornwall to the enchanted island of Corsica and, finally, to a breathtaking climax on the very doorstep of 10 Downing Street.